Soluble TWEAK is markedly upregulated in patients with ST-elevation myocardial infarction and related to an adverse short-term outcome - Chorianopoulos, Emmanuel; Jarr, Kai; Steen, Henning; Giannitsis, Evangelos; Frey, Norbert; Katus, Hugo (Atherosclerosis, 2010)
OBJECTIVE: Soluble TWEAK has recently been introduced as a potential mediator of cardiovascular disease. In this retrospective pilot study we thus sought to evaluate serum levels of soluble TWEAK (sTWEAK) patients with acute ST-elevation myocardial infarction (STEMI). - METHODS: Blood samples of 173 patients admitted to our hospital with acute STEMI (<24 h after symptom onset) were evaluated for their sTWEAK serum levels immediately at the time of admission and compared to those of patients with stable coronary artery disease (CAD) and healthy controls. Moreover, patients with STEMI were analyzed for their 30-day short-term outcome after acute STEMI. Adverse events were defined as the combined endpoint of cardiovascular death, resuscitation>24 h after reperfusion, cardiogenic shock or need for vasopressor therapy, repeated target vessel revascularization/myocardial infarction and stroke/TIA. - RESULTS: Patients with STEMI showed significantly higher levels of sTWEAK on admission compared to control patients or patients with chronic stable coronary artery disease (p<0.0001). Moreover, sTWEAK levels were higher in female patients. Additionally, sTWEAK levels were related to C-reactive protein levels and inversely correlated with the time between symptom onset and admission. Soluble TWEAK levels above the ROC-defined cutoff (>1286 pg/ml) significantly predicted an adverse short-term outcome in patients with STEMI after 30 days (p=0.0032). In this pilot study there was no significant relation between serum levels of sTWEAK and common risk factors like diabetes, hypertension, active smoking and age, white blood count or indices of myocardial function and damage like ejection fraction and infarct size in STEMI patients. Moreover, no significant relation was found between peak troponin T levels and sTWEAK on admission. - CONCLUSION: Our retrospective pilot study shows for the first time that sTWEAK is significantly elevated in patients with acute myocardial infarction compared to healthy controls and patients with stable coronary artery disease. Moreover, in our study sTWEAK levels on admission were associated with an adverse short-term outcome in STEMI patients. Further work is needed to precisely define the potential role of sTWEAK as a prognostic marker in myocardial infarction.